Characterization of Proliferating Lesion‐Resident Cells During All Stages of Atherosclerotic Growth. Issue 8 (15th August 2016) - Lhoták, Šárka; Gyulay, Gabriel; Cutz, Jean‐Claude; Al‐Hashimi, Ali; Trigatti, Bernardo L.; Richards, Carl D.; Igdoura, Suleiman A.; Steinberg, Gregory R.; Bramson, Jonathan; Ask, Kjetil; Austin, Richard C.
Abstract : Background: Monocyte recruitment leads to accumulation of macrophage foam cells and contributes to atherosclerotic lesion growth. Recent studies have reported that lesion‐resident macrophages can proliferate and represent a major cellular component during lesion development. This study was designed to assess whether the rate of macrophage proliferation changes during well‐established stages of lesion growth and to characterize other populations of proliferating cells within these lesions. Methods and Results: Using murine models of atherosclerosis ( Apoe −/− and LDLr −/− mice) and human coronary artery lesions, in situ proliferation of lesion‐resident cells at different stages of growth was assessed by staining for Ki67 and bromodeoxyuridine (BrdU). In early lesions, close to half of all actively growing macrophages were proliferating in situ. BrdU pulse labeling allowed for accurate identification of in situ proliferating macrophages compared to those derived from monocyte recruitment. Local macrophage proliferation declined as lesions advanced. Interestingly, intimal inflammatory cell infiltrates containing proliferating T lymphocytes were identified during the active phase of lesion growth and correlated with apoptotic cell death. Inflammatory cell infiltrates were completely resolved in advanced lesions and replaced with the necrotic core. Conclusions: Our findings indicate that atherosclerotic lesions contain locally proliferating macrophages primarily during early and intermediate stages of lesion growth. Furthermore, T‐lymphocyte‐enriched inflammatory cell infiltrates represent a novel subset of proliferating cells within the atherosclerotic lesion that correlate with apoptosis and precede the necrotic core. These findings have novel implications in understanding the pathogenesis of atherosclerosis and may implicate proliferating T lymphocytes as a contributing factor to lesion progression and stability.